2008
DOI: 10.1167/iovs.07-0586
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-Induced Contraction Is Not Promoted by Fibronectin-Fibronectin Receptor Interaction, or αSMA Expression

Abstract: A targeted inhibition approach demonstrated that key elements associated with transdifferentiation are not critical for TGFbeta-induced matrix contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…1B). This decrease in patch area was not attributable to losses in cell population by apoptosis or cell detachment from the culture dish (data not shown), but by matrix configuration and distribution changes in association with cells as previously determined by Dawes et al 28 using periodic acid Schiff (PAS) or aniline blue collagen staining. The addition of the broad-spectrum MMP inhibitor GM6001 (25 lM) resulted in no changes in patch area when compared with untreated control (Figs.…”
Section: Broad-spectrum Mmp Inhibition By Gm6001 Prevents Tgfb2-inducsupporting
confidence: 78%
See 1 more Smart Citation
“…1B). This decrease in patch area was not attributable to losses in cell population by apoptosis or cell detachment from the culture dish (data not shown), but by matrix configuration and distribution changes in association with cells as previously determined by Dawes et al 28 using periodic acid Schiff (PAS) or aniline blue collagen staining. The addition of the broad-spectrum MMP inhibitor GM6001 (25 lM) resulted in no changes in patch area when compared with untreated control (Figs.…”
Section: Broad-spectrum Mmp Inhibition By Gm6001 Prevents Tgfb2-inducsupporting
confidence: 78%
“…The assay previously described by Dawes et al 28 was employed to assess matrix contraction. FHL-124 cells were seeded at four distinct sites on a 35-mm tissue culture dish (Corning Incorporated Life Sciences, Corning, NY) at a density of 5000 cells/25 lL Eagle's minimum essential medium (EMEM) supplemented with 5% fetal calf serum (FCS, Gibco, Paisley, Scotland, UK) and 0.05 mg/mL gentamicin and maintained in a 358C, 5% CO 2 incubator until confluent patches spanning 5 mm developed.…”
Section: Patch Contraction Assaymentioning
confidence: 99%
“…To permit thorough investigations of the signalling pathways driving fibrotic events, human lens cell lines have been employed. Using this biological tool, specific assays have been developed to assess matrix production, transdifferentiation and matrix contraction (figures 6 and 7) [5,12,30]. Inhibition studies could then be employed to tease out the pathways mediating TGFb-induced fibrosis.…”
Section: Tgfb: the Orchestrator Of Fibrosismentioning
confidence: 99%
“…Moreover, it has been proposed that a5b1 integrin and fibronectin form a putative contractile apparatus with aSMA [132,133]. A recent study has investigated the putative role of fibronectin/fibronectin receptor interaction in relation to TGFb-induced matrix contraction by human lens epithelial cells [5]; application of an RGDS peptide to block the RGD binding site of a5 integrin revealed that the fibronectin/fibronectin receptor interaction was not required to promote matrix contraction by TGFb [5]. In addition, Marcantonio et al [134] demonstrated that a5b1 integrin expression was altered in FHL 124 cells following TGFb exposure, such that a diffuse pattern across the cell was observed, with membrane bound a5b1 integrin having no association with actin filaments.…”
Section: Extracellular Matrix/cell Communication-integrinsmentioning
confidence: 99%
See 1 more Smart Citation